Original articleMitofusin 2 expression dominates over mitofusin 1 exclusively in mouse dorsal root ganglia – a possible explanation for peripheral nervous system involvement in Charcot-Marie-Tooth 2A - Kawalec, Maria; Zabłocka, Barbara; Kabzińska, Dagmara; Neska, Jacek; Beręsewicz, Małgorzata (Folia Neuropathologica, 2014)
Mitofusin 2 (Mfn2), a protein of the mitochondrial outer membrane, is essential for mitochondrial fusion and contributes to the maintenance and operation of the mitochondrial network. Mutations in the mitofusin 2 gene cause axonal Charcot-Marie-Tooth type 2A (CMT2A), an inherited disease affecting peripheral nerve axons. The precise mechanism by which mutations in MFN2 selectively cause the degeneration of long peripheral axons is not known. There is a hypothesis suggesting the involvement of reduced expression of a homologous protein, mitofusin 1 (Mfn1), in the peripheral nervous system, and less effective compensation of defective mitofusin 2 by mitofusin 1. We therefore aimed to perform an analysis of the mitofusin 1 and mitofusin 2 mRNA and protein expression profiles in different mouse tissues, with special attention paid to dorsal root ganglia (DRGs), as parts of the peripheral nervous system. Quantitative measurement relating to mRNA revealed that expression of the Mfn2 gene dominates over Mfn1 mainly in mouse DRG, as opposed to other nervous system samples and other tissues studied. This result was further supported by Western blot evaluation. Both these sets of data confirm the hypothesis that the cellular consequences of mutations in the mitofusin 2 gene can mostly be manifested in the peripheral nervous system